Ramona the pest - Cleary, Beverly (New York : Scholastic, 1968)
Ramona the Pest, by Beverly Cleary, is the second book of the Ramona series and the first to focus on Ramona Quimby as the protagonist. This children's book chronicles the adventures of Ramona's first few months at kindergarten.